2002
DOI: 10.1103/physrevc.65.034907
|View full text |Cite
|
Sign up to set email alerts
|

Light nuclei production in heavy-ion collisions at relativistic energies

Abstract: We have measured the production of light nuclei (Aр3) in 11.6 GeV/c Au-Au collisions at the Brookhaven Alternating Gradient Synchrotron ͑AGS͒. The transverse mass spectra are analyzed using a thermal fireball model, and the yields for different particle species are discussed assuming coalescence and fragmentation as possible production mechanisms. The wide acceptance range of the 3 He measurements permits a broad study of the coalescence parameter B 3 as functions of transverse momentum and rapidity. Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…This parameter has been found to be constant at low transverse momentum in light-particle collisions [15,51]. In contrast, in AA collisions it has been reported that B A decreases with increasing centrality of the collision, and for each centrality it increases with p T [8][9][10][11].…”
Section: A Coalescence Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter has been found to be constant at low transverse momentum in light-particle collisions [15,51]. In contrast, in AA collisions it has been reported that B A decreases with increasing centrality of the collision, and for each centrality it increases with p T [8][9][10][11].…”
Section: A Coalescence Parametermentioning
confidence: 99%
“…Deuterons and antideuterons are copiously produced in heavy-ion collisions [1][2][3][4][5][6][7][8][9][10][11], but less abundantly in lighter particle collisions, such as pp [12,13] and pp [14] collisions, photoproduction γp [15], and e + e − annihilation at ϒ(nS) [16] and Z 0 [17] energies. Measurements of heavier antinuclei, such as antitritons and 3 He nuclei, have only been reported in pA [18,19] and AA collisions [11,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Equation (4) gives the yield normalized per trigger particle, the conventional normalization for dihadron correlations. In the case when the number of trigger particles that are not from hard processes is negligible, the yield is then the number of associated particles per jet.…”
Section: ηmentioning
confidence: 99%
“…The production of light (anti)nuclei is of interest in highenergy particle collisions because of the insight that these measurements can provide into particle production mechanisms [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Since the binding energies of light (anti)nuclei are on the order of a few MeV, they may be formed via coalescence of (anti)nucleons in the later stages of evolution of the system [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The production of light (anti)nuclei has been studied extensively at lower energies in Bevelac at LBNL [24,[46][47][48][49], AGS at RHIC [50][51][52][53], and SPS at CERN [54][55][56][57][58]. In the AGS 2 Advances in High Energy Physics experiments, it was found that the coalescence parameter ( 2 ) is of similar magnitude for both and indicating similar freeze-out hypersurface of nucleons and antinucleons.…”
Section: Introductionmentioning
confidence: 99%